The TV format market in Latin America: Trends and opportunities (2017)
The Latin American incursion and participation in the trade of audio-visual formats is considerably recent, and has become particularly relevant with the rise of the trade in scripted formats. The region’s expertise in telenovelas has given them an edge in this type of formats, with Argentina leading a conscious strategy to take advantage of the market that opened up following the international success of the Colombian Yo soy Betty, la fea (1999). We present here a summary of the latest developments of the format market in Latin America collected from trade magazine reports and in-depth interviews with leading figures in television production and distribution companies. Our research evinces that cultural proximity and volume of television production output are not necessarily predictors of the regional flow of scripted formats in the region.